(3GdEKHGJ GdLfGFi ddLQGFe GdEdcJQhfjI (B/s - (3EHQGgje dTHWs; (3CMeO YhV HdGd (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI ,s, 2021)
(3JYO GdLQGFe GdEdcJQhfjI feWkG ELQGejG LOjOG CaQRg GdJWhQ GdJcfhdhLi GdMOjK HaVd GdKhQI GdYdejI ai eLGd GdGJUGdGJ h GdeYdheGJ(B: (3HeG jJejR Hg ef YfUQi GdSQYI h GdObI ai JLejY GdeYdheGJ h JNRjfgG h eYGdLJgG(B: (3h ef Ke fbdgG h JHGOdgG Yf HYO(B: (3ShGA OGNd GdOhdI GdhGMOI(B: (3Ch Hjf Ohd YOI(B. (3h HGdQZe ef GdeRGjG GdcKjQI GdJi JMbbJ h JJMbb HaVd gPg GdKhQI ai cd efGMi GdMjGI GdYedjI(B: (3EdG Cfg h ai GdhbJ faSg JfWhi Ydi HYV GdLhGfH GdSdHjI(B: (3h GdJi JTcd JgOjOG NWjQG ddCef hGdGSJbQGQ ai GdeLJeY(B: (3h JJeKd gPg GdLhGfH GdSdHjI ai XghQ CfeGW LOjOI ef GdLQGFe CWdb YdjgG LQGFe JbfjI GdeYdheGJ(B: (3Ch GdLQGFe GdEdcJQhfjI(B: (3h GdJi JNJda cdjG Yf GdLQGFe GdJbdjOjI(B: (3ShGA ai CQcGfgG(B: (3Ch HjFJgG GdGaJQGVjI GddGeGOjI(B: (3Ch ai NUhUjI eQJcHjgG h CSGdjH GQJcGHgG(B: (3GdTiA GdPj cGf dg GfYcGS h CKQ cHjQ Ydi fUhU GdbGfhf GdLfGFi GdJbdjOi HTbjg GdehVhYi h GdELQGFi(B. (3h dgPG aCi eMGhdI dJWhjY gPG GdfeW GdELQGei h ENVGYg dELQGAGJ GdJMbjb GdJbdjOjI jDOi dG eMGdI Edi YOe GdEdJRGe HeJWdHGJ eHOC GdTQYjI GdELQGFjI(B: (3h SjLQ Ydi SdWGJ GdJMbjb GdcKjQ ef GdUYhHGJ h GdYbHGJ(B. (3h eY GeJOGO GdBKGQ GdSdHjI dgPg GdLQGFe Edi cGaI GdeLGdGJ(B: (3h JRGjO eYOdGJgG(B: (3SYJ GdOhd Edi JQTjO fUhU bhGfjfgG GdELQGFjI; dJJeGTi eY gPG GdfhY GdeSJMOK ef GdLQGFe(B: (3h Pdc Edi Mjf EQSGA fUhU bGfhfjI LOjOI JhGcH GdJWhQGJ h GdeJZjQGJ GdJi UGMHJ GdLQjeI(B. (3aEdi Ci MO jecf GdGYJeGO Ydi GdfUhU GdELQGFjI GdJbdjOjI decGaMI gPG GdfeW GdELQGei GdeJWhQ? Jdc gi GdETcGdjI GdJi MGhdoJ GdELGHI YdjgG ef NdGd gPg GdCWQhMIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi (B2021s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdEKHGJ GdLfGFis; (3GdLQGFe GdEdcJQhfjI s; (3GdbGfhf GdLfGFis; (3QSGFd LGeYjIs